Security in computing and communications : 4th International Symposium, SSCC 2016, Jaipur, India, September 21-24, 2016, Proceedings /: 4th International Symposium, SSCC 2016, Jaipur, India, September 21-24, 2016, Proceedings. (2016) - Unknown
No abstract available